The 17 March 2013 storm: Synergy of observations related to electric field modes and their ionospheric and magnetospheric Effects. Issue 11 (11th November 2016) - Lyons, L. R.; Gallardo‐Lacourt, B.; Zou, S.; Weygand, J. M.; Nishimura, Y.; Li, W.; Gkioulidou, M.; Angelopoulos, V.; Donovan, E. F.; Ruohoniemi, J. M.; Anderson, B. J.; Shepherd, S. G.; et al.
Abstract: The main phase of the 17 March 2013 storm had excellent coverage from ground‐based instruments and from low‐ and high‐altitude spacecraft, allowing for evaluation of the relations between major storm time phenomena that are often considered separately. The shock impact with its concurrent southward interplanetary magnetic field (IMF) immediately drove dramatic poleward expansion of the poleward boundary of the auroral oval (implying strong nightside reconnection), strong auroral activity, and strong penetrating midlatitude convection and ionospheric currents. This was followed by periods of southward IMF driving of electric fields that were at first relatively smooth as often employed in storm modeling but then became extremely bursty and structured associated with equatorward extending auroral streamers. The auroral oval did not expand much further poleward during these two latter periods, suggesting a lower overall nightside reconnection rate than that during the first period and approximate balance with dayside reconnection. Characteristics of these three modes of driving were reflected in horizontal and field‐aligned currents. Equatorward expansion of the auroral oval occurred predominantly during the structured convection mode, when electric fields became extremely bursty. The period of this third mode also approximately corresponded to the time of largest equatorward motion of the ionospheric trough, of apparent transport of high total electron content (TEC) features into the auroral oval from the polar cap, and of largest earthward injection of ions and electrons into the ring current. The enhanced responses of the aurora, currents, TEC, and the ring current indicate a common driving of all these storm time features during the bursty convection mode period. Key Points: Storm had excellent ground/space data coverage, allowing evaluation of relations between major storm phenomena often considered separately Identified three southward IMF electric fields driving modes that were reflected in the aurora and ionospheric and field‐aligned currents The third mode was extremely bursty, giving common driving of auroral and current structures, TEC changes, and ring current injection